2002
DOI: 10.1556/aphyt.37.2002.1-3.24
|View full text |Cite
|
Sign up to set email alerts
|

Examination of female proportion of light trapped turnip moth (Scotia segetum Schiff.)

Abstract: The change of the number of turnip moth (Scotia segetum Schiff.) females was examined at 65 different light trap stations between 1957 and 1990. There are two generations of the examined species in Hungary, but the individual number of the first generation is low year by year, so we processed only the data of the second generation.Only those generations were examined that had more than 100 samples because of the statistical reliability. Thirty-three light trap stations were suitable for this examination. The j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Long-term monitoring studies have observed sex ratio bias in a number of migratory insect species. The sex ratios of light-trapped insects have been found to differ among species 6,7 . Some studies have found that males are captured by light traps more frequently than are females in some nocturnal insect species 8 ; examples include Parnassius mnemosyne 9 , Scotia segetum 6 and Spodoptera exigua 10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-term monitoring studies have observed sex ratio bias in a number of migratory insect species. The sex ratios of light-trapped insects have been found to differ among species 6,7 . Some studies have found that males are captured by light traps more frequently than are females in some nocturnal insect species 8 ; examples include Parnassius mnemosyne 9 , Scotia segetum 6 and Spodoptera exigua 10 .…”
Section: Introductionmentioning
confidence: 99%
“…The sex ratios of light-trapped insects have been found to differ among species 6,7 . Some studies have found that males are captured by light traps more frequently than are females in some nocturnal insect species 8 ; examples include Parnassius mnemosyne 9 , Scotia segetum 6 and Spodoptera exigua 10 . However, female-biased migratory insect populations also exist, such as populations of Aphid parasites 11 , Aphidus avenae 12 , Sogatella furcifera and Nilaparvata lugens 13 .…”
Section: Introductionmentioning
confidence: 99%